2016
DOI: 10.1117/1.jbo.21.7.078002
|View full text |Cite
|
Sign up to set email alerts
|

Focused ultrasound-mediated sonochemical internalization: an alternative to light-based therapies

Abstract: Activation of sonosensitizers via focused ultrasound (FUS), i.e., sonodynamic therapy has been proposed as an extension to light-activated photodynamic therapy for the treatment of brain as well as other tumors. The use of FUS, as opposed to light, allows treatment to tumor sites buried deep within tissues as well as through the intact skull. We have examined ultrasonic activation of sonosensitizers together with the anticancer agent bleomycin (BLM), i.e., sonochemical internalization (SCI). SCI is a technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…FUS has been explored as a drug delivery platform for treating brain diseases [10] and involves in sonodynamic therapy (SDT) [11]. SDT relies on deep penetration of ultrasound (US) and tumor-specific accumulation of a sonosensitizer, has proved to be an effective, low-cost and safe anti-tumor therapy [12]. Our previous works on SDT have shown its anti-neoplastic effects on various cancers with great potential [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…FUS has been explored as a drug delivery platform for treating brain diseases [10] and involves in sonodynamic therapy (SDT) [11]. SDT relies on deep penetration of ultrasound (US) and tumor-specific accumulation of a sonosensitizer, has proved to be an effective, low-cost and safe anti-tumor therapy [12]. Our previous works on SDT have shown its anti-neoplastic effects on various cancers with great potential [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The results shown in Figure 5B, employing this model, demonstrated that SDT potentiated the cytotoxic effects of BLM to a significant degree. This was the case regardless of the sequence of SDT and BLM application, although SDT before drug was more effective [42,45]. This synergistic effect is postulated to be due to endosomal escape, in a similar manner to that seen for light-based PCI [46,47].…”
Section: Review Hirschberg and Madsenmentioning
confidence: 73%
“…In SCI experiments, Gonzales et al studied AlPcS 2a in combination with the anticancer drug, BLM [45]. BLM has had limited clinical use since it must be given in relative high concentrations and has a small therapeutic window.…”
Section: Endosomal Entrapmentmentioning
confidence: 99%
“…Moreover, compared with the Cy5-labeled PK group, the red signal intensity in cells incubated with Cy5-labeled PTPK under US irradiation is stronger (about 2-fold, Figure S6B), and more red fluorescence separates from the green fluorescence (LysoTracker) (lower overlap coefficient, Figure S6C), indicating that PTPK can easily enter cells and escape from the lysosomes into the cytoplasm during US treatment. US can enhance the cellular internalization of nanoparticles, which is known as ''sonochemical internalization,'' since the reactive oxygen species (ROS)-induced lipid peroxidation increases the membrane permeability (Gonzales et al, 2016). Furthermore, the self-assembled nanoparticles can be observed in the lysosomes by Bio-TEM, confirming the in situ self-assembly under US (Figure 2B).…”
Section: In Vitro Cytotoxicity Mechanism and Tissue Penetration Evaluationmentioning
confidence: 59%